Efficient Synthesis of Broadband Linear Frequency-Modulated Quadrature Signals for Coherent Electro-Optical Sensor Systems - Schmidt, Marius; Carlowitz, Christian (IEEE MTT-S International Microwave Symposium Digest, 2024)
This paper presents a novel approach to efficiently generate broadband, complex baseband, linear, frequency-modulated quadrature signals for driving quadrature mach-zehnder-modulators. In contrast to conventional approaches based on high sampling rate arbitrary waveform generators, cost and complexity is significantly reduced, while coherent distance and motion sensing is retained through single-sideband optical modulation. By using two FMCW synthesizers with contrary sweep rates and frequency crossing at half sweep duration, a zero-IF frequency ramp with unlimited relative bandwidth can be generated through I/Q-downconversion. Furthermore, sweep rate and bandwidth of the frequency ramp are doubled with this method compared to a single synthesizer. for experimental verification, an FMCW signal with 10 GHz bandwidth and a ramp duration of 32 μs has been generated using two 13-18 GHz PLL-based synthesizers. Coherent optical frequency domain ranging measurements at 1550 nm with different fiber lengths exhibit similar performance in terms of resolution and sensitivity compared to a two-channel 12 GS/s laboratory-grade AWG.
CRIS-Team Scopus Importer:2024-08-16
Keywords: electro-optical modulation; FMCW radar; frequency synthesis; microwave photonics